Lets say that the two unknown integers are
![n](https://tex.z-dn.net/?f=n)
and
![m](https://tex.z-dn.net/?f=m)
.
We know the following things about
![n](https://tex.z-dn.net/?f=n)
and
![m](https://tex.z-dn.net/?f=m)
:
![n+m=26](https://tex.z-dn.net/?f=n%2Bm%3D26)
![n^2+m^2=340](https://tex.z-dn.net/?f=n%5E2%2Bm%5E2%3D340)
And, we want to find
![nm](https://tex.z-dn.net/?f=nm)
.
To solve this, we'll use the expansion of the squared of the sum of any two inegers; this is expressed as:
![(n+m)^2=n^2+2nm+m^2](https://tex.z-dn.net/?f=%28n%2Bm%29%5E2%3Dn%5E2%2B2nm%2Bm%5E2)
So, given what we know about the unknown integers, the previous can be written as:
![(26)^2=340+2nm](https://tex.z-dn.net/?f=%2826%29%5E2%3D340%2B2nm)
We can easily solve for
![nm](https://tex.z-dn.net/?f=nm)
:
The answer is 168.
Another approach to solve the problem is, from the two starting equations, compute the values of
![n](https://tex.z-dn.net/?f=n)
and
![m](https://tex.z-dn.net/?f=m)
, which are 12 and 14, and directly compute their product; however, the approach described is more elegant.